KEPEMIMPINAN TRANSFORMASIONAL DALAM PENINGKATAN MUTU PENDIDIKAN DI MADRASAH TARBIYAH ISLAMIAH (MTI) - Syamsul Qomar (al-fikrah: Jurnal Manajemen Pendidikan, 2016)
From research conducted data showed that transformational leadership has been executed well by leaders in MTI Canduang. This is evidenced by the changes better than ever, morale and motivation of teachers and employees. Factors supporting leadership in MTI Canduang of which is a strong leader, the majority are young, energetic and highly motivated, skilled in the art, the support of all parties. Whereas the inhibiting factor of which is the absence of a permanent dormitory, minimal finances. Models/styles of verbal and non verbal leadership shown by the variety of writing programs that have been created by the leadership as well as attitudes and daily behavior is an example for subordinates. From the findings of this study concluded that transformational leadership has done well in MTI Canduang. Factors supporting leadership more than the barriers. While the verbal and non verbal leadership has been executed well by the existing leaders. Key Words: Kepemimpnan transformasional, peningkatan mutu